Planar and distorted indigo as the core motif in novel chromophoric liquid crystals. (17th August 2015) - Porada, Jan H.; Neudörfl, Jörg-M.; Blunk, Dirk
Abstract : The phase behaviour of calamitic indigoid liquid crystals was investigated and rationalised on the basis of a crystal structure analysis. Abstract : Symmetrically bis-substituted indigo derivatives with long peripheral alkyl chains were synthesised by the reductive condensation of corresponding isatin derivatives. Their thermotropic mesomorphism was investigated with respect to different substitution patterns, which include the position and lateral modifications of the substituents. A systematic investigation of structure–property relationships revealed that only substitution at the 6 and 6′ positions affords the calamitic shape necessary to form smectic or nematic liquid crystalline phases. This finding is rationalised on the basis of a structural analysis of N, N ′-diacetyl indigo and the consequences for 5, 5′- and 6, 6′-bis-substituted derivatives are discussed. Some of the liquid crystalline substances exhibit dichroism, which is especially pronounced in highly ordered phases. In addition, the 6, 6′ substitution leads to significantly enhanced activity with respect to the photochemical trans – cis isomerization of N, N ′-diacetylated indigo derivatives.